2021
DOI: 10.3390/s21175772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feature Selection Techniques for Power Amplifier Behavioral Modeling and Digital Predistortion Linearization

Abstract: The power amplifier (PA) is the most critical subsystem in terms of linearity and power efficiency. Digital predistortion (DPD) is commonly used to mitigate nonlinearities while the PA operates at levels close to saturation, where the device presents its highest power efficiency. Since the DPD is generally based on Volterra series models, its number of coefficients is high, producing ill-conditioned and over-fitted estimations. Recently, a plethora of techniques have been independently proposed for reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In addition, an integrated prognostic indicator consisting of multiple dimensions may help to reflect the real and complicated inflammatory and nutritional status ( 29 ). In the face of so many features, it is very important to eliminate over-fitting in feature selection ( 30 , 31 ). Published studies revealed that over-fitting might be solved by applying bootstrapping technique and LASSO Cox PH regression analysis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an integrated prognostic indicator consisting of multiple dimensions may help to reflect the real and complicated inflammatory and nutritional status ( 29 ). In the face of so many features, it is very important to eliminate over-fitting in feature selection ( 30 , 31 ). Published studies revealed that over-fitting might be solved by applying bootstrapping technique and LASSO Cox PH regression analysis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a first experiment, the pursuit algorithm of the Bayesian treatment proposed in this article will be contrasted with the OMP and DOMP techniques for the linearization of the commercial class AB PA under test with an average output power of 30.1 dBm and a gain compression of 2.34 dB. Comparison with these techniques is justified because the OMP is a reference in [15] and the DOMP has demonstrated superior performance compared to other algorithms [20].…”
Section: B Comparative Assessment Of the Sbp Versus Greedy Algorithms...mentioning
confidence: 99%
“…The vector containing the basis functions following the EGMP behavioral model described in ( 5 ) is , while is the vector of coefficients. As detailed in [ 23 ], feature selection techniques can be applied to select the most relevant basis functions and thus reduce the order of the original EGMP behavioral model.…”
Section: Envelope Tracking Pa Linearizationmentioning
confidence: 99%